2015
DOI: 10.1128/jvi.03340-14
|View full text |Cite
|
Sign up to set email alerts
|

Postchallenge Administration of Brincidofovir Protects Healthy and Immune-Deficient Mice Reconstituted with Limited Numbers of T Cells from Lethal Challenge with IHD-J-Luc Vaccinia Virus

Abstract: Protection from lethality by postchallenge administration of brincidofovir (BCV, CMX001) was studied in normal and immune-deficient (nude, nu/nu) BALB/c mice infected with vaccinia virus (VACV). Whole-body bioluminescence imaging was used to record total fluxes in the nasal cavity, lungs, spleen, and liver and to enumerate pox lesions on tails of mice infected via the intranasal route with 10 5 PFU of recombinant IHD-J-Luc VACV expressing luciferase. Areas under the flux curve (AUCs) were calculated for indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…The development of neutralizing antibodies to RPXV was monitored throughout this study and it was found that antibody titers, not present in any animal prior to infection, were present in all rabbits who survived to the scheduled termination with no difference in titers between placebo and BCV-treated animals. This observation is consistent with reports from other investigators that BCV did not interfere with formation of protective immunity following infection or vaccination in the mouse ectromelia and vaccinia models (Parker et al, 2014;Zaitseva et al, 2015). Hence patients infected with smallpox and treated with BCV would be expected to develop full protective immunity against subsequent smallpox infection.…”
Section: Discussionsupporting
confidence: 92%
“…The development of neutralizing antibodies to RPXV was monitored throughout this study and it was found that antibody titers, not present in any animal prior to infection, were present in all rabbits who survived to the scheduled termination with no difference in titers between placebo and BCV-treated animals. This observation is consistent with reports from other investigators that BCV did not interfere with formation of protective immunity following infection or vaccination in the mouse ectromelia and vaccinia models (Parker et al, 2014;Zaitseva et al, 2015). Hence patients infected with smallpox and treated with BCV would be expected to develop full protective immunity against subsequent smallpox infection.…”
Section: Discussionsupporting
confidence: 92%
“…In immunodeficiency studies, BCV provided partial protection to mice with moderate immunodeficiency (57-100% survived). However, it could only extend time to death in mice with severe immunodeficiency (84). Tecovirimat was protective in moderately immunocompromised mice but could only delay death when mice lacked both B and T cell immunity (95,110).…”
Section: Discussionmentioning
confidence: 99%
“…To model severe immunodeficiency, BALB/c mice lacking T cells were challenged with VV-IHD. Although all mice succumbed to disease, time to death was significantly delayed (84).…”
Section: Brincidofovirmentioning
confidence: 96%
See 1 more Smart Citation
“…A multitude of compounds have been evaluated for their ability to halt Orthopoxvirus replication. These include compounds which target host tyrosine kinases [ 123 ], viral DNA replication [ 124 , 125 ], viral transcription [ 126 , 127 ], and viral morphogenesis [ 128 , 129 , 130 , 131 , 132 , 133 ]. Amongst these compounds, two are at late stages of development.…”
Section: Anti-smallpox Chemotherapeuticsmentioning
confidence: 99%